2011
DOI: 10.1111/j.2044-8333.2011.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing training in juvenile corrections: A comparison of outside experts and internal trainers

Abstract: Purpose. This study was designed to compare expert consultant trainers and less experienced, in-house trainers in providing basic training in motivational interviewing (MI) for juvenile corrections employees.Methods. Trainees (n = 1,552) attended a 3-day workshop administered by either a member of the Motivational Interviewing Network of Trainers (MINT) or a corrections staff member who had been trained by a MINT trainer.Results. Pre-to post-test MI knowledge and skill gains did not vary between MINT expert an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is also possible that the soldiers were more skeptical of MT when delivered by the ME, given the ME's lack of knowledge about the military context. A similar interpretation was proposed by one TTT study on motivational interviewing (MI) in prisons (Doran et al 2013). Namely, Doran et al (2013) suggested that while expert consultants may have been better able to conduct MI, participants were skeptical of these trainers, given their lack of knowledge of the prison environment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is also possible that the soldiers were more skeptical of MT when delivered by the ME, given the ME's lack of knowledge about the military context. A similar interpretation was proposed by one TTT study on motivational interviewing (MI) in prisons (Doran et al 2013). Namely, Doran et al (2013) suggested that while expert consultants may have been better able to conduct MI, participants were skeptical of these trainers, given their lack of knowledge of the prison environment.…”
Section: Discussionmentioning
confidence: 81%
“…A similar interpretation was proposed by one TTT study on motivational interviewing (MI) in prisons (Doran et al 2013). Namely, Doran et al (2013) suggested that while expert consultants may have been better able to conduct MI, participants were skeptical of these trainers, given their lack of knowledge of the prison environment. Herein, the ME may have been more adept at delivery of MT principles, technique instruction, and execution guidance.…”
Section: Discussionmentioning
confidence: 81%
“…Scoring is divided into subcomponents that include attitudes consistent with MI, SA myths identified, behaviors consistent with MI (prescribed behaviors), and behaviors not consistent with MI (proscribed behaviors) . Internal consistency of the tool has been documented with a Cronbach's α of 0.84 …”
Section: Methodsmentioning
confidence: 99%
“…Due to the constraints of this particular environment (e.g., the inability to conduct individualized training and data collection), it is noteworthy this training modality demonstrated any effect on staff members’ delivery of praise statements. Typically, administrators in these settings provide training via didactic modalities (Lott, 2018) and subsequently evaluate training effects with indirect measures such as written quizzes (Doran et al, 2013; Masters et al, 2016).…”
Section: Discussionmentioning
confidence: 99%